Li2TiO3–LaSrCoFeO3 semiconductor heterostructure for low temperature ceramic fuel cell electrolyte. (6th April 2021) - Wang, Faze; Xing, Yueming; Hu, Enyi; Dong, Ting; Jiang, Zheng; Liu, Jingjing; Wang, Hao; Yang, Fan
Abstract: Semiconductor-based electrolytes have significant advantages than conventional ionic electrolyte fuel cells, especially for high ionic conductivity and power outputs at low temperatures (<600 °C). This work reports a p-n heterojunction composite electrolyte developed by a p-type La0.8 Sr0.2 Co0.8 Fe0.2 O3-δ (LSCF) and n-type Li2 TiO3 (LTO). It achieved a power output of 350 mW cm −2 at 550 °C using LSCF-LTO heterostructure as the electrolyte. On the other hand, pure LSCF and Li2 TiO3 were made as the fuel cell electrolyte as well. The former resulted immediately a short circuiting problem and exhibited no device voltage because of high electron (hole) conductivity. While the Li2 TiO3 can reach an open circuit voltage (OCV) but deliver too low power output, 37 mW cm −2 at 550 °C. Scanning Electron Microscope (SEM) combined with High-Resolution Transmission Electron Microscope (HR-TEM) clearly proved the formation of heterogeneous interface. Also, Fourier Transform Infrared Spectroscopy (FTIR) was performed to demonstrate the functional group of the synthesized materials. The results demonstrate clearly the semiconductor heterostructure effect. By adjusting apriority composition of the n-type and p-type components, electronic conduction is well suppressed in the membrane electrolyte. Meanwhile, by constructing p-n heterostructure and build-in field, we have succeeded in high ionic conductivity, high current and power outputs for the low temperature fuel cells. The results are interesting in general that to construct a p-n heterostructure electrolyte can be an effective and common way in developing low temperature ceramic fuel cells. Highlights: Suppressing electron short circuiting is realized by n-p heterojuction. LTO-LSCF composite as electrolyte for SIFC showed remarkable MPD of 350 mW cm −2 @ 550 °C. A methodology to construct enhanced ion conductivity LSCF-based SIFC is proposed. High ion conduction and suppressed electron conduction is realized by tailoring n-p junction.